2016
DOI: 10.1517/14712598.2016.1170804
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell derived secretome and extracellular vesicles for acute lung injury and other inflammatory lung diseases

Abstract: Introduction Acute respiratory distress syndrome is a major cause of respiratory failure in critically ill patients. Despite extensive research into its pathophysiology, mortality remains high. No effective pharmacotherapy exists. Based largely on numerous preclinical studies, administration of mesenchymal stem or stromal cell (MSC) as a therapeutic for acute lung injury holds great promise, and clinical trials are currently underway. However, concern for the use of stem cells, specifically the risk of iatroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 141 publications
1
130
0
7
Order By: Relevance
“…A number of studies have demonstrated the beneficial effects of MSC-EVs in vitro and in animal models of lung, kidney, and liver diseases [37,38]. Furthermore, several studies have shown that EVs exert their therapeutic effects by transferring their mRNA to diseased cells [20,29,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated the beneficial effects of MSC-EVs in vitro and in animal models of lung, kidney, and liver diseases [37,38]. Furthermore, several studies have shown that EVs exert their therapeutic effects by transferring their mRNA to diseased cells [20,29,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…According to the International Society for Stem Cell Research (ISSCR), MSCs are usually characterized based on the following three criteria: 1) plastic adhesion ability in standard culture; 2) non-expression or low expression of CD45, CD34, CD14, CD11b, CD79a, CD19, and HLA-DR and high expression of CD105, CD73, and CD90; and 3) ability to differentiate into osteoblasts, adipocytes, and chondrocytes in vitro. 21 Investigation of the morphology of the isolated cells showed that they displayed homogeneous elongated ( Figure 1A) structures, and the BMSCs expressed CD44, CD73, CD90, and CD105, but not CD45. These results showed that we successfully separated the BMSCs from the mice bone marrow ( Figure 1B).…”
Section: Identification Of Bmscs In Micementioning
confidence: 99%
“…Li et al demonsterated that intravenous use of MSCs in the treatment of acute pulmonary inflammation induced by H9N2 avian influenza in mice caused a significant reduction in plasma and BAL inflammatory factors (IL-1Îą, IL-6, TNF-Îą and IFN-Îł) and a the corresponding increase in anti-inflammatory cytokine (IL-10), 3 days after cell therapy. The researchers stated that this treatment method reduces the lung permeability and the concentration of the alveolar fluid proteins [52,81].…”
Section: The Effects Of Msc Therapy On Inflammation Factors In Bal Anmentioning
confidence: 99%